1970
DOI: 10.1007/bf01630518
|View full text |Cite
|
Sign up to set email alerts
|

Erbrütung der Eier von Dorsch(Gadus morhua), Flunder(Pleuronectes flesus) und Scholle(Pleuronectes platessa) unter kombinierten Temperatur- und Salzgehaltsbedingungen

Abstract: Rearing the eggs of cod (Gadus morbua), flounder (Pleuronectesflesus) and plaice (Pleuroneetes platessa) under combined temperature and salinity conditions. Eggs of Baltic cod (Gadus morhua L.), flounder (Pleuronectes flesus L.) and plaice (Pleuronectes pIatessa L.) have been reared under combined temperature and satinity conditions (0°-16 ° C, 7 %-42 %0 S). Combined temperature and salinity influences on embryonic development were investigated. Optimum temperatures for the rearing of cod eggs range from 4 o t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
54
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(61 citation statements)
references
References 27 publications
(6 reference statements)
7
54
0
Order By: Relevance
“…For example, flatfishes such as turbot (Psetta maxima), plaice (Pleuronectes platessa) and flounder (Platichthys flesus) or other fishes like cod (Gadus morhua), sprat (Sprattus sprattus) and herring (Clupea harengus) are distributed in the North Sea in an almost fully marine environment as well as in the brackish waters of the Baltic Sea. For this reason, stocks of the same species are specialised and adapted to prevailing hydrographical conditions in their habitat (Von Westernhagen 1970;Nissling andWestin 1991, 1997;Karås and Klingsheim 1997) and these adaptations are considered specific for the respective population as a result of long-term selection.…”
Section: Introductionmentioning
confidence: 99%
“…For example, flatfishes such as turbot (Psetta maxima), plaice (Pleuronectes platessa) and flounder (Platichthys flesus) or other fishes like cod (Gadus morhua), sprat (Sprattus sprattus) and herring (Clupea harengus) are distributed in the North Sea in an almost fully marine environment as well as in the brackish waters of the Baltic Sea. For this reason, stocks of the same species are specialised and adapted to prevailing hydrographical conditions in their habitat (Von Westernhagen 1970;Nissling andWestin 1991, 1997;Karås and Klingsheim 1997) and these adaptations are considered specific for the respective population as a result of long-term selection.…”
Section: Introductionmentioning
confidence: 99%
“…Although the hydrographical situation in the western Baltic Sea is characterised by a high variability of the essential reproduction parameters salinity, temperature and oxygen content Matthäus et al, 1994Matthäus et al, , 2000, Bleil and Oeberst (2000) showed that the hydrographical conditions varied in ranges which did not influence the fertilisation and the development of spawned eggs negatively. According to Westernhagen (1970), Graumann (1974), Westin and Nissling (1991), Nissling et al (1994) and Nissling and Westin (1997), salinity is a major factor which influences the fertilisation of cod eggs in the Baltic Sea. Eggs spawned by the Belt Sea cod need a salinity of more than 14 PSU (marine condition).…”
Section: Discussionmentioning
confidence: 99%
“…Both are known to affect the spawning behaviour of adult fish and, in addition, have relevance to development, hatching success and vertical distribution of fish eggs (Westernhagen 1970). It is therefore likely that the occurrence of species in the samples was influenced by the hydrography.…”
Section: Designation Of Areasmentioning
confidence: 99%